Cooperative mechanisms of oxygen vacancy stabilization and migration in the isolated tetrahedral anion Scheelite structure. Issue 1 (December 2018) - Yang, Xiaoyan; Fernández-Carrión, Alberto; Wang, Jiehua; Porcher, Florence; Fayon, Franck; Allix, Mathieu; Kuang, Xiaojun
Abstract Tetrahedral units can transport oxide anions via interstitial or vacancy defects owing to their great deformation and rotation flexibility. Compared with interstitial defects, vacancy-mediated oxide-ion conduction in tetrahedra-based structures is more difficult and occurs rarely. The isolated tetrahedral anion Scheelite structure has showed the advantage of conducting oxygen interstitials but oxygen vacancies can hardly be introduced into Scheelite to promote the oxide ion migration. Here we demonstrate that oxygen vacancies can be stabilized in the BiVO4 Scheelite structure through Sr2+ for Bi3+ substitution, leading to corner-sharing V2 O7 tetrahedral dimers, and migrate via a cooperative mechanism involving V2 O7 -dimer breaking and reforming assisted by synergic rotation and deformation of neighboring VO4 tetrahedra. This finding reveals the ability of Scheelite structure to transport oxide ion through vacancies or interstitials, emphasizing the possibility to develop oxide-ion conductors with parallel vacancy and interstitial doping strategies within the same tetrahedra-based structure type. Fast oxide ion conductors are the key materials for some technological devices. Here the authors report the creation and stabilization of oxygen vacancies in BiVO4 Scheelite with isolated tetrahedral anion structures for improved ionic conducting performance and understanding of the conduction mechanism.